2023
DOI: 10.1021/acs.jafc.2c07624
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Growth-Dependent System to Regulate Cell Growth and Keratinase Production in B. subtilis

Abstract: Keratinases specifically degrade insoluble keratin waste, thus contributing to environmental protection and sustainable biomass development. However, their industrial application is hindered by inefficient enzyme production and poor biomass generation. In this study, the heterologous expression of keratinase was found to have cytotoxicity and might block host cell growth due to its proteolytic property. To address this problem, an autoregulatory expression system based on quorum sensing was developed to synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The main factors that may affect the yield and production rate depend upon the choice of appropriate host for preparing recombinant enzyme protein that is expressed in bacteria strains like lactic acid bacteria, Bacillus and Escherichia coli, it would be used in Pichia pastoria (yeast) and Aspergillus (fungi) ( Liu et al, 2013 ; Hou et al, 2019 ).In a bacterial host, it's more convenient to express recombinant enzyme protein as it cannot over express large proteins that may need to post translational modifications ( Gong et al, 2020 ; Ruiz-Villafán et al, 2023 ).Through xylose inducible expression arrangements in B. megaterium and E.coli ; keratinase of Bacillus licheniformis was cloned successfully with the use of 17 promotors ( Radha and Gunasekaran 2007 ; Gong et al, 2020 ). Response surface methodology ( RSM ) had been used to maximize the process that inference in 3-time high keratinase production through B. megaterium (pWHK3 recombinant than that of strain B. licheniformis MKU3 ( Radha and Gunasekaran 2007 ; Tian et al, 2019 ; Su et al, 2023 ). Many studies have reported the different factors affecting the keratinase enzyme activity of different strains of bacteria on various waste products of poultry industry.…”
Section: Use Of Genetically Modified Microbial Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors that may affect the yield and production rate depend upon the choice of appropriate host for preparing recombinant enzyme protein that is expressed in bacteria strains like lactic acid bacteria, Bacillus and Escherichia coli, it would be used in Pichia pastoria (yeast) and Aspergillus (fungi) ( Liu et al, 2013 ; Hou et al, 2019 ).In a bacterial host, it's more convenient to express recombinant enzyme protein as it cannot over express large proteins that may need to post translational modifications ( Gong et al, 2020 ; Ruiz-Villafán et al, 2023 ).Through xylose inducible expression arrangements in B. megaterium and E.coli ; keratinase of Bacillus licheniformis was cloned successfully with the use of 17 promotors ( Radha and Gunasekaran 2007 ; Gong et al, 2020 ). Response surface methodology ( RSM ) had been used to maximize the process that inference in 3-time high keratinase production through B. megaterium (pWHK3 recombinant than that of strain B. licheniformis MKU3 ( Radha and Gunasekaran 2007 ; Tian et al, 2019 ; Su et al, 2023 ). Many studies have reported the different factors affecting the keratinase enzyme activity of different strains of bacteria on various waste products of poultry industry.…”
Section: Use Of Genetically Modified Microbial Strainmentioning
confidence: 99%
“…The integrated vectors containing kerA, either with or without the P43-promoter, were created and subsequently subcloned into Bacillus subtilis DB104 and B. licheniformis T399D. Southern blot analysis was used to identify and determine the presence of multiple copies of kerA integration into the chromosome in T399D ( Rahimnahal et al, 2023 ; Su et al, 2023 ). Three to 5 copies were found to be the ideal range for kerA integration.…”
Section: Use Of Genetically Modified Microbial Strainmentioning
confidence: 99%
“…20 In the process of feed pelleting, there is a short step involving a high-temperature steam process, which requires a certain degree of heat resistance for the keratinases; moreover, the dehairing step in the leather industry and the keratinases in the washing industry both require resistance alkali. 21 Along with the modification of the extremophilicity of keratinases, acid and alkali resistance, high temperature resistance, and protease resistance will be the main directions of keratinase modification. Many agricultural and industrial applications have used microbial-produced keratinases in recent decades.…”
Section: Introductionmentioning
confidence: 99%